Establishment of salivary tissue-organoid biorepository: characterizing salivary gland stem/progenitor cells and novel differentiation marker PSMA/FOLH1 - Syed Mohammed Musheer Aalam; Ana Rita Varela; Aalim Khaderi; Ronsard J. Mondesir; Dong-Gi Mun; Andrew Ding; Isabelle M. A. Lombaert; Rob P. Coppes; Chitra Priya Emperumal; Akhilesh Pandey; Jeffrey R. Janus; Nagarajan Kannan (npj Regenerative Medicine)
Abstract The salivary gland (SG) is vital for oral function and overall health through secretion of saliva. However salivary dysfunction due to aging, medications, autoimmune disorders, and cancer treatments poses significant challenges. We established the first diverse and clinically annotated salivary regenerative biobank at Mayo Clinic to study salivary gland stem/progenitor cells (SGSPCs). Optimization of cell isolation and progenitor assays revealed SGSPCs enriched within the CD24/EpCAM/CD49f+ and PSMA- phenotypes of both submandibular and parotid glands, with clonal differentiation assays highlighting heterogeneity. Induction of PSMA/FOLH1 expression was associated with SGSPC differentiation. Using mass spectrometry-based single cell proteomics, we identified 2461 proteins in SGSPC-enriched cells, including co-expressed cytokeratins, expressed in rare salivary ductal basal cells. Additionally, PRDX, a unique class of peroxiredoxin peroxidases enriched in SGSPCs, demonstrated H2O2-dependent growth, suggesting a role in salivary homeostasis. These findings provide a foundation for SGSPC research and potential regenerative therapies for salivary gland dysfunction.